Development and innovation of technological networks in some peripheral urban areas - Luca Ruggiero (European Regional Science Association (ERSA), 2004)
The society that emerged out of the crisis of the fordist model of production and organisation of space is increasingly dominated by development, innovation and diffusion of urban technological networks (telecommunications, transport, energy, etc.). There are nowadays, working at different geographical scales, an amount of projects to increase the number of networks and connect a larger number of people and organisations. This is based on the notion that the emergence of an internationally-integrated and increasingly urbanised Network Society would allow better connection between the local and the global level and vice versa, giving those marginal areas the opportunity to take part to the main development dynamics. The rise of the network society is also often associated with a regeneration of the local administrations, in ways that would make them more efficient and clear, improving territorial government and citizens quality of life. Besides, the development of the `digital city' seems to be connected with the emergence of new professional careers and a virtual space interacting community that would help to better meet the needs of local society and increase the level of participation to territorial government decision making. On the opposite side some authors argue that the contemporary conditions of development and innovation of infrastructure networks world-wide are particularly favourable to `secessionary tendencies' and lead to the deliberate creation of premium networks that selectively tend to connect together only the most favoured users and places. In the present paper I will analyse these contradictory tendencies attributed to the development and innovation of infrastructure networks operating within and between cities. I will concentrate mainly on the experience of some, considered, marginal urban realities of the Mediterranean area.
Keywords: 330